User-Centered Feature Requirements in Wearable Digital Health to Support Self-Care Among Stroke Survivors - Merita Arini; Moch Zihad Islami; Attar Husna Fathiya; Warih Andan Puspitosari; Nurchayati Nurchayati; Firman Pribadi; Winny Setyonugroho (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Stroke is a major cause of death and disability in Indonesia, leaving many survivors with long-term self-care challenges. Wearable technologies using digital health technology offer potential support. However, the adoption of technology is hindered by usability, accessibility, and cultural barriers. This study explores user-driven feature requirements to inform inclusive and effective digital self-care solutions for stroke survivors Methods: This explorative qualitative study with a phenomenological approach involved in-depth interviews with 19 stroke survivors conducted between May and August 2024 in Yogyakarta and Bandung. Participants were selected using purposive and snowball sampling and analyzed using thematic analysis. Ethical approval was obtained from the Universitas Aisyiyah Yogyakarta Ethics Committee (No. 3832/KEP-UNISA/VII/2024), and all participants provided informed consent. Results: A total of 19 stroke survivors (mostly male and aged 45–60) participated in this study, with the majority having lived with stroke for over five years. Two overarching themes emerged. The first, Managing Health and Daily Life, reflected the need for features that assist stroke survivor to navigate their self-care practices. The second, Navigating Technology with Limitations, highlighted emotional and socio-cultural barriers that hinder technology adoption and sustained use among stroke survivors. These findings suggest that effective wearable solutions must integrate practical health management functions with user-centered design, addressing cognitive, emotional, and contextual barriers to long-term use, with implications for inclusive design guidelines and grassroots-based technology policies. Conclusion: This study gives an understanding of user-centered perspectives in digital health technology by highlighting the practical and emotional aspects of technology use. Future research should incorporate caregiver and healthcare provider perspectives and evaluate prototypes in real-world settings to strengthen inclusive innovation and sustainable adoption.